Obesity Practice of Sports for Health, Smoking, Hypokinetic Diseases and Dietary Habits of the Teachers of Physical Education in Jordan - Jafar Al Arjan (My University, 2013)
The study aims at identifying the prevalence rates of obesity and overweight, underweight and the extent of the practice of sports for health, smoking, and diseases associated with sedentary and some dietary habits of physical education teachers in Jordan. The sample consists of (861) teachers randomly selected from various public, private and UNRWA schools in Jordan measuring their weight, height and responce to the questionnaire measure (the practice of sport for health, smoking, diseases associated with sedentary and some dietary habits, daily). The results indicated that the prevalence of obesity among male teachers was (13.38%), and the female teachers was (14.41%), with an average of (14.75%), and that (26.6%) of the male teachers and (7.5%) of the female teachers were smokers. Im both sex the percentage was (20.1%). The average number of cigarettes smoked by male teachers (22.7± 5.19), and female teachers was (13.4 ± 4.19) with an average smoking of (21.52 ± 5.94) cigarettes /day. The study shows that (35.82%) of male smoking teachers do smoke before their students, While female teachers do not do that.. (60.21%) of the male teachers and (35.84%) of the female teachers practice sports once or more /week.  The most common diseases among physical education teachers are low back pain by (5.45%), for male teachers, and the percentage (16.04%) for the female teachers. With a general average of (9.05%). Diabetes (4.2%) (4.1%) (4.2%), blood pressure (3.0%), (4.1%), (3.48%), rheumatism and diseases of the joints (0.7%) (1.7%), (1.04%), cardiovascular diseases (0.70%), (0.68%), (0.69%) respectively. While the persentage of those who know that they had a higher risk in the level of blood fats (4.57%), (11.26%), (6.85 %), respectively. The study also indicated the presence of high rates of spread of some unhealthy eating habits among teachers and that they should not have breakfast, a lot of tea, coffee, soft drinks and not eat vegetables, fruits, milk. To sum up, the spread of these risk factors among physical education teachers should be of interest by the decision-maker because of its relation to the trends of students and health practices.